Analisis Pengaruh Kepemilikan Manajerial, Keberagaman Gender, dan Modal Intelektual Terhadap Nilai Pasar - Bagus Ahmad Mahardhika; Erliana Banjarnahor (MANAJEMEN, 2026)
This study aims to analyze the effect of managerial ownership, gender diversity, and intellectual capital on the market value of financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Market value is used as an indicator that reflects investors' perceptions and expectations of the company's performance and prospects. This study uses a quantitative approach with panel data regression methods. The sample was determined using purposive sampling techniques for financial sector companies that met the data completeness criteria. The data used was secondary data obtained from companies' annual reports and financial reports. Managerial ownership was measured based on the proportion of shares owned by management, gender diversity was measured through the representation of women in the management or board structure, while capital was measured using the Value Added Intellectual Coefficient (VAIC) approach. The results of the study indicate that managerial ownership, gender diversity, and intellectual capital have a positive and significant effect on company market value. These findings emphasize the importance of corporate governance and intangible asset management in increasing the valuation of financial sector companies.